A Phase 1 first‐in‐human study of the safety, tolerability, and pharmacokinetics of the ROBO2 fusion protein PF‐06730512 in healthy participants - Chay Ngee Lim; Constantino Kantaridis; Isabelle Huyghe; Donal Gorman; Stephen Berasi; Gabriele E. Sonnenberg (Wiley, 2021)
Abstract Proteinuria associated with podocyte effacement is a hallmark of focal segmental glomerulosclerosis (FSGS). Preclinical studies implicated ROBO2/SLIT2 signaling in the regulation of podocyte adhesion, and inhibition of this pathway is a novel target to slow FSGS disease progression. This first‐in‐human dose‐escalation study evaluated the safety, tolerability, pharmacokinetics, and immunogenicity of PF‐06730512, an Fc fusion protein that targets the ROBO2/SLIT2 pathway, in healthy adults. In this Phase 1, double‐blind, sponsor‐open study, single ascending dose (SAD) cohorts were randomized to receive up to 1000 mg or placebo intravenously (IV); multiple ascending dose (MAD) cohorts were randomized to receive up to 400 mg subcutaneous (SC) doses, 1000 mg IV dose, or matching placebo. Safety evaluations were performed up to 71 (SAD) and 113 (MAD) days after dosing; blood samples were collected to measure serum PF‐06730512 concentrations and antidrug antibodies (ADA) to PF‐06730512. Seventy‐nine participants (SAD, 47; MAD, 32) were enrolled. There were 108 mild (SAD, 46; MAD, 62) and 21 moderate (SAD, 13; MAD, 8) treatment‐emergent adverse events (TEAEs); no deaths, treatment‐related serious AEs, severe TEAEs, or infusion reactions were reported. PF‐06730512 exposure generally increased in an approximately dose‐proportional manner; mean t1/2 ranged from 12-15 days across 50-1000 mg doses. Immunogenicity incidence was low (SAD, 0 ADA+; MAD, 2 ADA+). In conclusion, single IV doses of PF‐06730512 up to 1000 mg and multiple IV and SC dosing up to 1000 and 400 mg, respectively, were safe and well tolerated in healthy participants. Further trials in patients with FSGS are warranted. Clinical trial registration: Clinicaltrials.gov: NCT03146065.